KUALITAS PENGELOLAAN PELAYANAN ANGGOTA PADA UNIT KOPERASI SIMPAN PINJAM DELTA WIRA DANA PURWOSARI KABUPATEN PASURUAN - Ika Rohmatul Umah; Rossa Ilma Silfia (Halu Oleo University, 2025)
This study aims to determine the quality of member service management at the Delta Wira Dana Purwosari Savings and Loans Cooperative Unit, Pasuruan Regency. This research uses qualitative methods, with data collection techniques through observation, interviews, and documentation studies. The results of the research through the analysis of the TERRA and SERVQUAL models show that the quality of service at KSP Delta Wira Dana still requires comprehensive improvement. The weakest dimensions are in responsiveness and assurance. Although the Tangibles or physical facilities of the cooperative are generally considered adequate, Empathy is still questionable because of the lack of consistency of cooperative managers in serving members and services are still general and formal, without considering the specific conditions of each member, such as economic status, financial literacy, or business difficulties. So it is concluded that KSP Delta Wira Dana should immediately improve service quality, especially in the absence of an emergency response system and low transparency of information.